Engineering mechanics an introduction to dynamics - McGill, David J. (PWS series in engineering., 1995)
The principles of statics and dynamics are applied in order to understand the behaviour of bodies in motion, displaying engineering mechanics principles and supported with worked examples. This text is supplemented with figures which develop important concepts using commonplace objects.